Third-Party Punishment Mechanism and Corporate Cooperation in Environmental Investment: Experiments on Public Goods Game - Yuling Liao; Liang Zhang; Siying Lei; Meizhe Song; Wenkang Deng; Daofu Hu (Discrete Dynamics in Nature and Society)
In the context of corporate environmental investment (EI), this paper designs an experiment on public goods game without punishment and an experiment on that game with third-party punishment (TPP). Then, the influence of IEP and TPP mechanism on corporate EI behaviors was tested in details. The results show that different enterprises vary in IEP and took heterogenous behaviors in the two corporate EI experiments; the introduction of TPP pushed up the environmental resource investment of enterprises and increased the success rate of EI cooperation; IEP and TPP exerted a significantly positive influence on corporate EI behaviors; the introduction of TPP, coupled with the consideration of corporate IEP, can effectively elevate corporate EI and improve the eco-environment.